Features of Anthropometric Indicators of Athletes and Students who do not Play Sports in Men in The Conditions of Karakalpakstan (Journal of Pedagogical Inventions and Practices, 2023)
The article considers the features of somatometric indicators in men engaged in sports in the environmental conditions of the Republic of Karakalpakstan.